2020
DOI: 10.1136/bmjpo-2020-000846
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills with children in paediatric anaesthesia: challenges while wearing a face mask

Abstract: Effective communication with children is a skill, the importance of which is especially highlighted by the COVID-19 pandemic and the ubiquitous wearing of face masks. Anaesthesiology consultants have been shown to display excellent communication skills that facilitate the development of rapid rapport and patient cooperation. Good communication results in positive interactions for hospitalised children, which correlates with improved healthcare outcomes. However, interactions with a child aren’t always straight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Still, as studies suggest, people can make recourse to other non-verbal signals in their interlocutor in order to shortcut the concealed face expressions and decipher their emotions, such as voice [36], gaze direction and head orientation [37] or body posture [38], or even through the articulation of the speech and the increase in the speech volume [39]. This might prove of utmost importance, especially in cases of emergency, such as the COVID-19 pandemic, when we are forced to wear face masks, and many researchers have advanced some ways in which communication can be enhanced, either in personal [40] or professional encounters [41][42][43]. Among these are the use of the upper part of the face (eyes and eyebrows) to counteract the shielded part or the resort to transparent face masks or to telecommunication.…”
Section: Literature Review 21 Use Of Face Masks In Interpersonal Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, as studies suggest, people can make recourse to other non-verbal signals in their interlocutor in order to shortcut the concealed face expressions and decipher their emotions, such as voice [36], gaze direction and head orientation [37] or body posture [38], or even through the articulation of the speech and the increase in the speech volume [39]. This might prove of utmost importance, especially in cases of emergency, such as the COVID-19 pandemic, when we are forced to wear face masks, and many researchers have advanced some ways in which communication can be enhanced, either in personal [40] or professional encounters [41][42][43]. Among these are the use of the upper part of the face (eyes and eyebrows) to counteract the shielded part or the resort to transparent face masks or to telecommunication.…”
Section: Literature Review 21 Use Of Face Masks In Interpersonal Communicationmentioning
confidence: 99%
“…Among these are the use of the upper part of the face (eyes and eyebrows) to counteract the shielded part or the resort to transparent face masks or to telecommunication. As for the professional encounters, there is much more research done than for interpersonal relationships and it has been carried out mainly on the communication between doctors and patients in healthcare settings [41][42][43][44]. It seems that the wearing of face masks poses real communication challenges and presents not only a physical [45], but also a psychological barrier [46] in the doctor-patient relationship, especially for patients with cognitive or hearing problems, leading to disruptions in this type of professional communication, which should be based on trust and empathy, i.e., to anxiety, stress, frustration, fatigue, both for the speaker and the listener [47].…”
Section: Literature Review 21 Use Of Face Masks In Interpersonal Communicationmentioning
confidence: 99%
“…The hindering effect of face masks on accurate emotion recognition may be especially relevant in interpersonal relations at the workplace where appropriate social interaction is expected. Furthermore, concerns on how face masks might (harmfully) impact child development have been voiced and it has been suggested that certain communication techniques might be important to ensure effective communication with children further on [4]. Effects of face masks are also relevant in the context of mental disorders: Individuals with emotional processing alterations such as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mask-wearing has been highlighted as hindering communication in paediatric anaesthesia. 5 In our experience, although powered airpurifying respirators allow patients to visualise staff faces without obstruction, improving visual cues, this benefit is pitted against the background noise of the respirator creating communication difficulties. This is more keenly felt with anxious patients who might be softly spoken.…”
Section: Parentsmentioning
confidence: 89%